2017
DOI: 10.1016/j.artd.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A simple technique to remove well-fixed acetabular components in revision of total hip arthroplasty

Abstract: Removing well-fixed acetabular components can be a challenge for orthopaedic surgeons in revision of total hip arthroplasty. Acetabular bone loss, fracture, and other complications occurred in extracting implants may result in instability and fail of revision. Thus, instruments are developed to avoid such complications. We report a simple technique by drilling a tunnel on the superolateral quadrant of acetabulum and using an offset staff to remove acetabular components without many matching units. The procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Zhang, et al described a technique of drilling a tunnel on the postero-superior quadrant of acetabulum, from the bone cortex to the surface of acetabular metal cup [11]. Whilst this technique may seem relatively simple, it can result in weakening of the posterior wall of the acetabulum.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Zhang, et al described a technique of drilling a tunnel on the postero-superior quadrant of acetabulum, from the bone cortex to the surface of acetabular metal cup [11]. Whilst this technique may seem relatively simple, it can result in weakening of the posterior wall of the acetabulum.…”
Section: Surgical Techniquementioning
confidence: 99%
“…6,19 In the setting of revision THA, the double socket technique may mitigate bone loss, prolonged operative time, blood loss, and debris generation associated with the replacement of incompatible well-fixed acetabular shells or those with failed locking mechanisms. 10,20 Furthermore, the double socket technique provides an opportunity to perform limited adjustments in liner angulation and offset relative to the well-fixed shell, thereby attaining a cup orientation and position that are more conducive to hip stability. 10,15 The results of the current study demonstrated that in contrast to our initial hypothesis, a significant…”
Section: Group Comparison Relative To Neutral (Group 1)mentioning
confidence: 99%
“…6,7 While poor acetabular component position may predispose a patient to recurrent instability after revision THA, the removal of well-fixed yet sub-optimally placed shells is associated with significant morbidity and bone loss. 5,8,9 Therefore, the cementation of the outer metallic liner of DM cups to a well-fixed acetabular shell (metal-in-metal constructs), also known as the double socket technique, is an alternative that has progressively gained recognition. 5,8,10 This technique allows partial correction of the acetabular position and orientation.…”
Section: Introductionmentioning
confidence: 99%